The factors that influence adherence of pregnant women with HIV/AIDS to anti-retroviral therapy - doi:10.5020/18061230.2011.p396 - Valéria Lima de Barros; Maria Alix Leite Araújo; Maria Natália Araújo de Alcântara; Marilene Alves Oliveira Guanabara; Simone Paes de Melo; Suzyanne da Silva Sobreira Guedes (Universidade de Fortaleza, 2012)
Objective: To learn the experiences of pregnant women with HIV/AIDS in relation to adherence to antiretroviral therapy in two public hospitals of reference for HIV/AIDS in Fortaleza-CE, Brazil. Methods: A descriptive study conducted with 24 pregnant women who were in prenatal care and use of antiretroviral therapy. Sociodemographic and obstetric data and information regarding the experience with antiretroviral therapy adherence were collected from July to September 2009, through a semi-structured interview. Results: Women had a mean age of 29, low income, low education and a stable partner. It was found that some factors affect pregnant women adherence to antiretroviral therapy. Among these, stand out not accepting the diagnosis and the absence of signs and symptoms of AIDS. However, the fear of transmitting the virus to the baby acted as a stimulus for pregnant women adhere to treatment. Conclusion: The non-acceptance of diagnosis and the absence of signs and symptoms of AIDS negatively affect pregnant women adherence to antiretroviral treatment. On the other hand, the fear that the child be born with the virus and the desire to continue to live are stimuli to adherence.